#### Simplify \frac{a^{-5}}{a^{3}} and express the answer using positive exponents.

Anonymous

0

Sangeetha Pulapaka

0

STEP 1: Recall what are exponents

https://www.qalaxia.com/viewDiscussion?messageId=5cdad642f32dc9584bdccefe

STEP 2: Recall what are positive exponents

https://www.youtube.com/watch?v=1XUefcEqFsM

STEP 3: Recall what are the rules of exponents

https://www.qalaxia.com/viewDiscussion?messageId=5cdad460f32dc9584bdccec7

STEP 4: Simplify

\frac{a^{-5}}{a^{3}} = a^{-5}.a^{-3} (according to the quotient rule)

= a^{-8}=\frac{1}{a^{8}} ( according to the negative exponent rule)